Novel RET mutations in Hirschsprung's disease patients from the diverse South African population - Julies, Monique G; Moore, Sam W; Kotze, Maritha J; du Plessis, Lana (European journal of human genetics : EJHG, 2001)
Hirschsprung's disease (HSCR) is a common cause of intestinal obstruction in neonates with an incidence of one in 5000 live births. The disease occurs due to the absence of parasympathetic neuronal ganglia in the hindgut, resulting in irregular or sustained contraction of the affected segment. DNA samples of 40 unrelated subjects with HSCR were subjected to mutation screening of the RET (REarranged during Transfection) proto-oncogene, the major susceptibility gene for HSCR. Five novel (V202M, E480K, IVS10-2A/G, D771N, IVS19-9C/T) and one previously described mutation (P973L) were identified. Only two of the mutation-positive patients (from different ethnic groups) displayed total colonic aganglionosis, and both were heterozygous for mutation D771N. The potential disease-causing mutations occurred in 20% of individuals, with more males (22.5% representing seven of 31 males) affected than females (12.5% representing one of eight females). This study represents the first comprehensive genetic analysis of this disease in the diverse South African population.